An Analytical Hierarchy Process (AHP) Approach to Road Maintenance Prioritization: A Case Study in Shan State, Myanmar - Nandar Tun; Kyaing Kyaing; Moe Thet Thet Aye (Innovation in Engineering, 2024)
Maintaining rural roads plays an important role in the development of society and economy in Shan State, Myanmar. This study aims to prioritize road maintenance by employing the Analytical Hierarchy Process (AHP). There are four types of pavement distress: roughness, raveling, potholes, edge failure, and bleeding. Data collection was conducted and analyzed in ten rural roads by using an Excel-based tool to evaluate the AHP analysis. The findings significantly discussed awareness of road conditions and pavement maintenance requirements, and R4 had the highest level of priority to maintain. The study also compared the Pavement Condition Index (PCI) method with AHP results, highlighting acceptance and differences. Significant differences were noted for others due to the comprehensive nature of AHP when both methods ranked R5 and R6 typically within the top three. This research provides a systematic and transparent approach for prioritizing road maintenance, enhancing resource optimization and decision-making. Both AHP and PCI methods are integrated, and a comprehensive way is recommended to ensure thorough assessment and optimal use of resources to plan road maintenance. The study also contributes to improving the sustainability and performance of the rural road network, supporting broader economic and social goals in Shan State, Myanmar.